Activity Profiles of Successful and Less-successful Semi-elite Rugby League Teams - Hulin, B. T.; Gabbett, T. J. (International Journal of Sports Medicine, 2015)
This study investigated whether match intensities during predefined periods differed among successful and less-successful rugby league teams. 4 semi-elite rugby league teams were split into ‘high-success’ and ‘low-success’ groups based on their success rates. Movement was recorded using a global positioning system (10 Hz) during 20 rugby league matches. Following the peak ball-in-play time period, the high-success group was able to maintain ball-in-play time that was: (1) 22% greater than the low-success group (P=0.01) and (2) greater than their mean period of match-play (P=0.01). In the peak and mean periods of match play, hit-up forwards from the high-success group covered less total distance (P=0.02; P=0.01), less high-intensity running distance (P=0.01; P=0.01) and were involved in a greater number of collisions (P=0.03; P=0.01) than hit-up forwards from the low-success group. These results demonstrate that greater amounts of high-intensity running and total distance are not related to competitive success in semi-elite rugby league. Rather, competitive success is associated with involvement of hit-up forwards in a greater number of collisions and the ability of high-success teams to maintain a higher ball-in-play time following the peak period. Strength and conditioning programs that: (1) emphasize high-intensity running and neglect to combine these running demands with collisions, and (2) do not offer exposure to match specific ball-in-play time demands, may not provide sufficient physiological preparation for teams to be successful in rugby league.
Keywords: time-motion analysis; performance; team sport